Kebahagiaan Karir pada Ibu Tunggal Bekerja - Firstara Lawindo; Fattah Hanurawan; Gamma Rahmita Ureka Hakim (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2020)
This study aims to find out the career happiness of a single mother working. The model used in this study is a qualitative research method. Data collection uses interviews, observation, and questionnaires to determine the consistency of answers. Data analysis techniques use thematic analysis techniques. To find out the validity of the data by checking the answers during the interview and compared with the answers to the questionnaire. This research was carried out in the city of Malang and Malang district with the number of three single mothers participants. This research is expected to be a new knowledge for both students and the people out there that being a single mother is not easy. A single mother really needs the support and affection of the people around her. For other researchers who want to do research on happiness with single mothers working, researchers should use the background of participants to be the same single mother and the existence of age criteria in the selection of participants so that it can provide better and more diverse research results.